Sistem Validasi Keaslian Dokumen Digital Berbasis QR-Code - Rakhmat Kurniawan R; Rina Filia Sari; Noor Azizah (Universitas Asahan, 2020)
Abstract – The prolonged Covid-19 pandemic forces each individual to minimize physical contact with other individuals to reduce its spread. The impact created by this restriction is the paralysis of all operational activities from all fields, especially education. All learning activities and academic services cannot be done face to face. To maintain their existence and total paralysis, all institutions have begun to switch their operational systems from offline to online. In tertiary institutions, especially at the State Islamic University of North Sumatra, Medan, learning is transferred using e-learning. However, the academic service system is done manually via chat and email applications. The use of chat and email communication applications in carrying out academic service operations is deemed quite helpful. The obstacle experienced by using these applications is the validation of documents sent by students to the academic or study program. The potential for document forgery using these applications is considered very vulnerable. To minimize document falsification, a system was created that could issue a QR-Code and embedded it into a digital document, where the QR-Code could be verified to determine the validity of the digital document. QR-Code issuance is done using a web-based application using the Codeigniter framework. By using a QR-Code-based validation system, it is hoped that the potential for document forgery can be minimized.Keywords – QR-Code, Authenticity of digital documents, Codeigniter Abstrak – Pandemi Covid-19 yang berkepanjangan memaksa setiap individu untuk meminimalisir kontak fisik dengan individu lainnya untuk mengurangi penyebarannya. Dampak yang dimunculkan oleh pembatasan ini adalah lumpuhnya seluruh kegiatan operasional dari seluruh bidang, terutama Pendidikan. Seluruh kegiatan pembelajaran dan pelayanan akademik tidak dapat dilakukan dengan bertatap muka. Untuk menjaga eksistensi dan kelumpuhan total, seluruh lembaga mulai beralih sistem operasionalnya dari offline menjadi online. Pada Perguruan Tinggi khususnya di Universitas Islam Negeri Sumatera Utara Medan, pembelajaran dialihkan dengan menggunakan elearning. Namun untuk sistem pelayanan akademis dilakukan secara manual melalui aplikasi chat dan email. Penggunaan aplikasi-aplikasi komunikasi chat dan email dalam melaksanakan operasional pelayanan akademik dirasa cukup membantu. Kendala yang dialami dengan menggunakan aplikasi-aplikasi tersebut adalah validasi keabsahan dokumen yang dikirimkan mahasiswa ke bagian akademik ataupun prodi. Potensi pemalsuan dokumen dengan menggunakan aplikasi-aplikasi tersebut, dirasa sangat rentan. Untuk meminimalisir pemalsuan dokumen, dibuatlah suatu sistem yang dapat menerbitkan QR-Code dan ditanamkan kedalam dokumen digital, dimana QR-Code tersebut dapat di verifikasi untuk mengetahui keabsahan dokumen digital tersebut. Penerbitan QR-Code dilakukan dengan menggunakan aplikasi berbasis web dengan menggunakn framework codeigniter. Dengan menggunakan sistem validasi berbasis QR-Code ini diharapkan potensi-potensi pemalsuan dokumen dapat diminimalisir.Kata kunci – QR-Code, Keaslian Dokumen Digital, Codeigniter